Towards development of a liposome-based vaccine to combat Clostridium difficile infection - Palazi, Panayiota (2021)
Antimicrobial resistant infections are now one of the most serious global threats due to the misuse of commonly prescribed antimicrobial agents. This crisis has led researchers towards the development of alternative methods of action. Treatment of Clostridium difficile, a bacterium with growing hyper-virulent strains causing thousands of deaths annually, is attracting widespread interest. The purpose of this study is to design and develop a vaccine against this enteropathogen using liposomal formulations as both the delivery system and as an adjuvant. A synthetic lipid linker bearing a maleimide group is used to mimic the natural presentation of several antigenic lipoproteins successfully expressed aiming at blocking all disease stages. Attention is focused on characterisation and optimisation of liposomal structures and formulation reactions using a number of analytical techniques including DLS and FACS.